Analisis Tentang Tanggungjawab Hukum Terhadap Perjanjian Kredit Pemilikan Rumah (KPR) - Permatasari, Raden Roro Faradilla Arina; , Nuswardhani, S.H.,S.U (2017)
This study aims to khow the process of agreement in home ownership credit. Because of that actions then the binded side have to responsible of the losses. Location of this study in Bank BTN Syariah Surakarta Branch coorporate with PT. Aristo KurniaAlam as the developer in providing decent houses to stay for low income communities. The method of the study is normative with the descriptive study because it will divide thoroughly and systematic about KPR. Data source is focus in literature research aim to find the secondary data with primary legal materials. The result of this study show that the process of credit agreement could underwent if the term and codition has been fulfilled according civil law however otherwise regulated by the bank. With this agreement, it will effect the rights and obligations for all sides. Then the legal liability appears in the connection of a mistakes that did by the a side that do not undergo their obligations. Mistakes could grounded by default because break the agreement dan Unlawful Acts. Keywords: Home Ownership, Credit Agreement, Liability